2000
DOI: 10.1590/s0034-71082000000200009
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive strategy of Leporinus friderici (Characiformes, Anostomidae) in the Paraná River basin: the effect of reservoirs

Abstract: The reproductive strategy of a species depends upon the interaction between intrinsic and extrinsic factors. Examining the population of Leporinus friderici in two reservoirs of the Upper Paraná River basin in reference to first gonadal maturation and breeding season and sites, the present investigation tested whether the environment formed by damming promoted spatial and temporal changes in the reproductive strategy of this species. Analyses of sex ratios showed that females significantly predominated in Itai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 13 publications
1
20
0
3
Order By: Relevance
“…Mature and spent females were registered in the winters of 2001, 2003, and 2005, albeit in small numbers. Lopes et al (2000) also reported cyclical changes in the duration and intensity of the reproductive period for Leporinus friderici in the Itaipu Reservoir. Acestrorhynchus pantaneiro presented a long reproductive period, similar to other species of peixe-cachorro, such as Galeocharax knerii (Magalhães et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Mature and spent females were registered in the winters of 2001, 2003, and 2005, albeit in small numbers. Lopes et al (2000) also reported cyclical changes in the duration and intensity of the reproductive period for Leporinus friderici in the Itaipu Reservoir. Acestrorhynchus pantaneiro presented a long reproductive period, similar to other species of peixe-cachorro, such as Galeocharax knerii (Magalhães et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the differentiated growth rates, the high mortality of males, the high longevity of females or even the susceptibility to the fishing equipment used may explain the predominance of females (Abilhoa & Agostinho, 2007). It could even be associated with the abundance of available food (a response of the species to this condition) (Lopes et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, after the implementation of a reservoir, a restructuration of the fish community will contribute to the reduction and/or the disappearance of species, including reophilic ones, in addition to probably producing an increase in species adapted to lentic environments , which present a high physiological tolerance and behavioral adaptability, leading to plasticity and, consequently, reproductive success (Gray et al, 2000;Lopes et al, 2000;Mammoliti, 2002;Dias et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the length structure between females and males are common in fish populations and reflect growth rate differences between sexes (Sparre & Venema, 1997). These differences have been observed for other species of Leporinus in the Upper Paraná River basin reservoirs, such as Leporinus friderici in the Itaipu and Corumbá reservoirs (Lopes, Benedito-Cecilio, & Agostinho, 2000), and L. ambryrhynchus in the Miranda Reservoir (Vono, Silva, Maia, & Godinho, 2002). Significant differences in length structure were not observed between female and male L. piau at the Pau dos Ferros Reservoir, indicating that the growth rate was similar for both genders.…”
Section: Discussionmentioning
confidence: 74%